Effect of High Pressure Processing (HPP) and Pulsed Electric Field (PEF) on Digestibility of New Zealand Chilled Lamb - Tao, Yue (Auckland University of Technology, 2016)
Lamb is one of the widely consumed meats in New Zealand owing to its flavor and high nutritional value such as protein, mineral and vitamins. Recently, High Pressure Processing (HPP) and Pulsed Electric Field (PEF) have been adopted in processing lamb with the advantage of extending the shelf life without reducing the quality. The aim of the project was to examine one of the attributes of nutritional quality of lamb, "digestibility". Digestibility of different lamb cuts at different phases of simulated digestion (undigested, gastric and intestinal, S1, S2 and S3, respectively); the effect of HPP and PEF treatments on digestibility of lamb; storage effect for PEF treated lamb on digestibility have been investigated. The supply of lamb may not be able to meet the demand, using HPP and PEF treatments may be worth investigating. Studies examining the digestibility of meat, practically lamb, and treated (HPP and PEF) lambs, are missing in the literature. This was the first study to investigate the FAAs of HPP and PEF treated lamb cuts after the in vitro digestion. The amount of FAAs in the lamb cuts is different. Some lamb cuts are ignored by the consumers though they are still nutritionally valuable to contribute to human health. This was another important part in my research. In this project, examinations of the physical properties of lamb samples such as color, moisture and pH, were also studied. An in vitro digestion model was used to simulate the digestion of the processed (HPP and PEF) lamb. Nineteen free amino acids (FAAs), including 9 essential and 10 non-essential amino acids, were identified and quantified in both HPP and PEF lamb samples using EZ-faast kit and GC. For the HPP treated lamb, the total FAAs in three different digestion phases (S1, S2 and S3) of two lamb cuts (rump and knuckle) were significantly different from one another (P < 0.05). The lamb cuts were significantly affected (P < 0.05) by the high-pressure treatments, in terms of digestibility. The total FAAs of rump and knuckle increased from 200 MPa to 300 MPa, and decreased from 300 MPa to 600 MPa in S1, S2 and S3. The same pattern was observed with most of the nineteen individual FAAs as well. Different cuts also affected both total FAAs and individual FAAs significantly (P < 0.05). The high-pressure condition affected the pH significantly (P < 0.05) for both cooked rump and knuckle lamb cuts. Lamb samples processed at higher pressure levels (600 MPa) had higher L* and b * values. Moisture content of the lamb samples differed largely (P < 0.05) with high-pressure treatments. For PEF treated lamb, the total FAAs found in the three digestion phases of the seven lamb cuts (bolar, rump, knuckle, full back, cube roll, shanks and flat) differed significantly (P < 0.05) from each other. The storage time (0 day: samples were stored at -20?C immediately after the slaughter. 7 days: samples were stored at 4°C for 7 days and then stored at -20°C until further analysis) had a significant effect (P < 0.05) on the amount of FAAs present at all digestion phases (S1, S2 and S3) for both non-PEF and PEF treated lamb. The amount of total FAAs differed depending on the lamb cuts, for all three phases of digestion significantly (P < 0.05) as well. For the color, the lightness increased, redness and yellowness decreased from 0 day to 7 days for both non-PEF and PEF treated lamb. Moisture for some cuts showed significant difference (P < 0.05) with respect to the storage time (0 day and 7 days).
Keywords: HPP; PEF; Lamb; Digestion